A Alfabetização Emergente na Educação Infantil e no 1º Ciclo do Ensino Básico em Moçambique - Inruma, Juvenal Maricane M. (2006)
This study results from the learning difficulties in reading and writing at school, its relationship with the oral language acquisition process in families. The object of this study, therefore, is Emergent Literacy (EL) and its relationship between oral language and the learning of reading and writing. Thus, the aim was to reflect on the Emergent Literacy process in the Nursery School Educatio n (NSE) and in the first cycle of the Lower Primary School in Mozambique. The study will give awareness to curriculum planners and teachers to develop oral language as a useful ability for reading and writing. Theoretically, the work will contribute to ana lyze and propose the forms of oral language as an invaluable tool to effectively and efficiently foster reading and writing in the first stages of schooling. Refer to PIAGET (1982); TEALE and SULZBY (1992); VYGOTSKY (1999); FERREIRO (2001) and TEBEROSKY and COLOMER (2003). This research is qualitative with a phenomenal character which was carried out in two stages: 1) first, an exploratory micro-study was done based on the interview and observation. This stage gave evidence on the existence of oral resources in the Lower Primary School Children s families; 2) the second stage involved a documental study consisting of analyzing Syllabi and Handbooks of the Nursery School Education and Monolingual Handbooks of the Lower Primary School. This dissertation concludes that in the Nursery School Education, both the Syllabi and the handbooks do not lead children to develop specific oral activities bearing in mind the different developmental stages of the child. The Lower Primary School Syllabi (1st and 2nd grades) are unrelated to the handbooks as regards the oral resource for learning reading and writing. This dissertation is in three chapters anticipated by an introduction and at the end are the conclusion, suggestions, appendices, annexes and references. Chapter 1 is about the exploratory micro-study; Chapter 2 reviews the theoretical framework of emergent literacy and Chapter 3 describes and analyzes EL and the 1st Cycle of the Lower Primary School